Vonoprazan - a new drug for inhibiting gastric acid secretion - Niewęgłowski, Kacper; Wilczek, Natalia; Rycharski, Michał; Niewęgłowska, Julita (Journal of Education, Health and Sport, 2022)
Introduction and purpose Vonoprazan is a potassium-competent acid blocker (P-CAB). It has the potential to be an alternative to proton pump inhibitors (PPIs) as it inhibits hydrochloric acid secretion. The mechanism of action is different than PPIs - vonoprazan reversibly inhibits gastric H+, K+-ATPase, while PPIs irreversibly. Vonoprazan is approved for use in Japan and the US. The aim of the study was to review articles on the use of vonoprazan instead of PPIs in the treatment of acid-related gastrological diseases and to present the results obtained. A brief description of the state of knowledge Vonoprazan is used in the treatment of acid-related gastrological diseases. The 20 mg dose is suitable for most diseases, such as treatment of ulcers during low-dose aspirin treatment, post-endoscopic submucosal dissection (post-ESD) ulcers, erosive esophagitis (EE) in gastroesophageal reflux disease (GERD), and Helicobacter pylori eradication. Summary Researches suggest that the drug is an alternative for PPIs and can be used instead of them. The main advantage of this drug over PPIs is that it works faster, more potent and long-lasting. Studies suggest that vonoprazan can be use to treatment of the acid-related diseases and may be a better choice than PPIs. Vonoprazan may have a particular use in the treatment of PPI-refractory GERD. In post-ESD ulcers, a significant benefit in treatment effects of vonoprazan over PPIs cannot be clearly concluded.